Expressive Speech In “To All The Boys: Always And Forever” - Safira Ade Purnama; Ni Luh Putu Krisnawati; Novita Mulyana (Fonologi: Jurnal Ilmuan Bahasa dan Sastra Inggris, 2024)
This study explores how expressive speech acts are used in the teen romantic comedy movie "To All the Boys: Always and Forever," directed by Michael Fimognari. Using Searle's theory of expressive speech acts and Yule's framework for direct and indirect speech acts, the study analyzes the female main character's speech acts through a descriptive qualitative approach. The study identifies few instances of expressive speech acts, with doubting speech being the most frequent. It also discovers that direct speech acts are more widely used than indirect ones. These findings contribute to the understanding of expressive speech acts in film, specifically how emotions and attitudes are conveyed through conversation.